2012
DOI: 10.1063/1.4732859
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of inherent structures to detect long-range correlations in supercooled liquids

Abstract: We propose deformations of inherent structures as a suitable tool for detecting structural changes underlying the onset of cooperativity in supercooled liquids. The non-affine displacement (NAD) field resulting from the applied deformation shows characteristic differences between the high temperature liquid and supercooled state, which are typically observed in dynamic quantities. The average magnitude of the NAD is very sensitive to temperature changes in the supercooled regime and is found to be strongly cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 61 publications
8
32
0
Order By: Relevance
“…So it is natural to expect that inherent structures have a close relation to our glassy structural order. For exam-ple, the similarity between our results for static growing length and those obtained by Mosayebi et al [355] suggests such a relation. There is certainly a connection, but here we mention a few important difference.…”
Section: Relation Between Glassy Structural Order and Inherent Structsupporting
confidence: 91%
See 1 more Smart Citation
“…So it is natural to expect that inherent structures have a close relation to our glassy structural order. For exam-ple, the similarity between our results for static growing length and those obtained by Mosayebi et al [355] suggests such a relation. There is certainly a connection, but here we mention a few important difference.…”
Section: Relation Between Glassy Structural Order and Inherent Structsupporting
confidence: 91%
“…[296] found a diverging static lengthscale by analysing the response of the inherent structure to static perturbation. Similarly, for binary hard and soft sphere mixtures, no local ordering, nor structural lengthscale has been found to accompany the growing dynamical lengthscale [353,306,351,354], but again Mosayebi et al found the opposite for the latter mixture [355]. The presence of a growing static length in Kob-Andersen and repulsive binary mixtures has also been reported by Karmakar and Procaccia [356].…”
Section: Counter Examples For the Scaling Relationmentioning
confidence: 69%
“…The discrepancy observed by most between structural and dynamic lengthscales in the T T MCT range is indicative that more is at play than structure, at least in the first few decades of dynamic slowing which are described by mode-coupling theory. However, it has been shown again and again [82,83,86,143,248,260,261,326,327,368,369,394,442,473,488,507,570] that the structure of deeply supercooled liquids is distinct from that of high temperature liquids and that particular locally favoured structures correspond to dynamically slow particles [300,326,327,394,473,507]. Along with others [86], we believe any coincidence in structural and dynamic lengthscales in the dynamical regime accessible to simulation may be obscured by the mode-coupling transition and that to resolve this question deeper supercooling is required.…”
Section: Static and Dynamic Correlation Lengthssupporting
confidence: 50%
“…However, as discussed in section V C, this simultaneous increase has certainly not universally been found, especially in d = 3. Indeed, while some groups have identified a concurrent increase of structural and dynamic lengthscales [261,300,368,369,442,507], the majority seem to find that the dynamic correlation length as determined by the four-point correlation length ξ 4 increases faster than the static length, sometimes even in the same system [86,138,218,255,256,277,326,416,500].…”
Section: Discussionmentioning
confidence: 99%
“…Returning to the idea of a thermodynamic transition, a key aspect is some kind of structural change. While such structural changes appear to be minor when looking at two-point measures like the structure factor, higher-order measures reveal a richer behavior [20][21][22][23][24][25]. In particular, the population of geometric motifs, so-called locally favoured structures (LFS), show a strong temperaturedependence [20].…”
Section: Introductionmentioning
confidence: 99%